2016
DOI: 10.5694/mja16.00445
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in acute in‐hospital cardiovascular care for Aboriginal and non‐Aboriginal South Australians

Abstract: Objectives: To assess differences in the rates of angiography and subsequent revascularisation for Aboriginal and non‐Aboriginal South Australians who presented with an acute coronary syndrome (ACS); to explore the reasons for any observed differences. Design: Analysis of administrative data with logistic regression modelling to assess the relationship between Aboriginal status and the decision to undertake diagnostic angiography. A detailed medical record review of Aboriginal admissions was subsequently under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 12 publications
(27 reference statements)
0
30
2
Order By: Relevance
“…11 However, disparities in ACS care for Indigenous people are well documented. 12 Here, we present a practical application of the guidelines for use in the Indigenous setting. 13 Indigenous patients who present to a health care facility with a suspected ACS must have access to a digital 12-lead ECG, which can, if necessary, be transmitted to a referral centre for assistance with decision making.…”
Section: Diagnosismentioning
confidence: 99%
“…11 However, disparities in ACS care for Indigenous people are well documented. 12 Here, we present a practical application of the guidelines for use in the Indigenous setting. 13 Indigenous patients who present to a health care facility with a suspected ACS must have access to a digital 12-lead ECG, which can, if necessary, be transmitted to a referral centre for assistance with decision making.…”
Section: Diagnosismentioning
confidence: 99%
“…Integrating cultural safety in an active manner reconfigures health care to allow greater equity of realised access, rather than the assumption of full access, including procession to appropriate intervention. As an example of the need to improve equity, a South Australian study found that Indigenous people presenting to emergency departments with acute coronary syndrome were half as likely as non‐Indigenous patients to undergo angiography 7 . More broadly, Indigenous people admitted to hospital are less likely to have a procedure for a condition than non‐Indigenous people 8…”
mentioning
confidence: 99%
“…As an example of the need to improve equity, a South Australian study found that Indigenous people presenting to emergency departments with acute coronary syndrome were half as likely as non-Indigenous patients to undergo angiography. 7 More broadly, Indigenous people admitted to hospital are less likely to have a procedure for a condition than non-Indigenous people. 8 Cardiovascular disease is the leading cause of death in Indigenous Australians.…”
mentioning
confidence: 99%
“…Cardiovascular disease is the leading cause of death among Indigenous and non‐Indigenous Australians. Coronary artery disease (CAD) mortality is estimated to be twice as high in Indigenous than non‐Indigenous Australians, and Indigenous Australians are affected at an age that is, on average, 10–15 years younger than non‐Indigenous Australians 1 . Rheumatic heart disease, now rare in the Western world, continues to affect Indigenous Australians at disproportionate levels.…”
mentioning
confidence: 99%
“…The disparities in both coronary artery and valvular disease contribute significantly to the gap in life expectancy between Indigenous and non‐Indigenous Australians. Despite this, studies have shown that rates of diagnostic coronary angiography, percutaneous coronary intervention and coronary artery bypass grafting are all lower for Aboriginal Australians, when compared with their matched non‐Indigenous counterparts 1 . A number of factors contribute to the marked disparities in incidence and treatment of cardiovascular disease among Indigenous and non‐Indigenous Australians.…”
mentioning
confidence: 99%